If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(5x+7)=3(2x+2)
We simplify the equation to the form, which is simple to understand
2(5x+7)=3(2x+2)
Reorder the terms in parentheses
+(+10x+14)=3*(2x+2)
Remove unnecessary parentheses
+10x+14=+3+*(+2x+2+)
Reorder the terms in parentheses
+10x+14=+(+6x+6)
Remove unnecessary parentheses
+10x+14=+6x+6
We move all terms containing x to the left and all other terms to the right.
+10x-6x=+6-14
We simplify left and right side of the equation.
+4x=-8
We divide both sides of the equation by 4 to get x.
x=-2
| 1/42+8=12 | | 2/8+3/4=w/6 | | y+13=8 | | P=3xyz+2y-5 | | 7z^4-84z^3+189z^2=0 | | 10x-6y+5x= | | y+2x=500 | | -1/8+1/2x=-59/8 | | 0.5x-3=11 | | 7x+x=6x+3+5x | | 96=35+c | | 0.5x-3=11 | | 7-8x=-41 | | 4y-5=13y+31 | | 10x+6y-5x= | | 6n+18=3n+72 | | 10=-3x+5x | | -3/5(x+1)=2 | | 3x-6y-9y+4x+8= | | 5/6x+2=-8 | | q+2.7=0.9 | | (9y-5)=(5-y) | | -5(t-5)+9t=6t-5 | | 10y+14x=170 | | 4/5(x-2)=-8 | | -5/6x+1=-19/6 | | 2x+6=-9x-7 | | 3/4(x+7)=6 | | -9=-6a-3a | | x(2-1)-23=-2 | | 5/2x3/5+4/3x2/5 | | 3.75(q-5)=4(q+3) |